Perancangan dan Pembuatan Website pada Komunitas Discerning Universitas Kristen Petra - Imanuel Friendly Lawalata; Adi Wibowo; Alexander Setiawan (Jurnal Infra, 2014)
The advancement of technology today has helped the widespread of internet among ordinary people in the society. The promotion of various goods, service, and information could be done easily using the internet. Internet is also easily accessible and usable anywhere, as long as the network is available.Inspired by the concern of the students involved in the campus ministry, a community is formed to bring about a positive cultural change in Petra Christian University. The philosophy of the community is to be a community of a disciples of Jesus, concerned in world's problems, longing to bring God's transformation. The community is called "Discerning", derived from the word "discern", which means a sharp observation and understanding.This website is being developed as another mean to provide informations about the Discerning Journals to the larger society outside the university's community. One of the focus in the development of this website would be to provide an outlet for students to read and produce journals. Therefore the website is developed and designed according to achieve that goal.